CREATE INDEPENDENT AND QUALIFIED YOUTH IN AN EFFORT TO PREVENT TEENAGE HEALTH PROBLEMS AND CHILD MARRIAGE THROUGH YOUTH POSYANDU - AZIZAH, NUR; Muhidayati, Wiwik; Luluk, Sri; Utami, Wiwik (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: Adolescence is a transition period from child to adult, and during this period adolescents often experience changes both physically, mentally and socially. The lack of knowledge of adolescents regarding adolescent reproductive health influences adolescent behavior in maintaining their reproductive health, apart from that this is also the cause of high levels of child marriage so it is necessary to increase the understanding and knowledge of adolescents regarding reproductive health and prevention of child marriage through activities at adolescent posyandu Method: community service is carried out through youth posyandu activities with socialization and education related to reproductive health and child marriage, where previously a pre-test was carried out regarding adolescent reproductive health material and after the activity a post-test was carried out. Result: community service activities were attended by 25 teenagers, midwives and village nurses, the majority, namely 18 teenagers (72%) had good understanding, this increased when compared to the pretest results, namely only 6 teenagers (24%) had good knowledge Conclusion: community service activities entitled creating independent and quality teenagers in an effort to prevent teenage health problems and child marriage through youth posyandu succeeded in increasing teenagers' understanding regarding reproductive health and child marriage